lexical conjunction Another reading in light of the rules of the text - Jabbar Kadhem Dawood Al-Omairi, Emad (Journal of College of Education, 2021)
Language, as a means of communication, takes from its social context a field of action, with a cogged contract, humility and use. There is no language that leads to a meaning based on a meaning with a media purpose, or a communicative and influential goal, except for that field and its procedural authority, that social authority that determines It has - the meaning - its features, and it has its systemic, semantic and pragmatic systems, and the rule in each: is “understanding and understanding”. Perhaps reading the lexical casting formats, in a blog towards the text, is one of the best levels that express the description of the text being a culture, based on references and assets, through which revealing visions appear about the thinking of its users, and their ability to manage and act in life; Because it is the motive for attracting things from the world of matter and experience, after referring them outside, to the world of symbol, meaning and thought in the text. Limiting the mechanisms that have been put in place to describe the lexical casting/combining in the modern linguistics of the text is a waste of what is in its fundamental formation in the first nucleus: the sentence, from the text, and what was presented in the text lesson is nothing but an easy attempt that requires another reading that repeats the text what I have been saying From the description of the first sentence, because the initial lexical structure is the ruling on what follows from the description